Family planning provision in the Trent health region: Is it accessible to school aged teenagers?. Issue 1 (1st January 2001) - Allen, Jane; Bradley, Sue
Abstract : Strategies to combat existing high teenage pregnancy rates in the UK need to include contraceptive services that can be easily accessed by young people, including those who are still at school. This study concerns the availability of family planning services to young people who are still at school. One hundred and eight family planning clinics in the Trent region were surveyed to determine their clinic opening hours. Hours accessible to school aged young people were identified as being services provided during school lunch breaks, after school and at weekends. A total of 498 weekly hours of provision were identified, and 260.5 of these were accessible to school aged young people. There was a lot of variation between health authority areas both in terms of the number of hours accessible to this age group and also in terms of the percentage of clinics not offering any service accessible to school aged people. The recent report from the Social Exclusion Unit identified accessible contraceptive services as part of its strategy to reduce teenage pregnancy rates in the UK. Although these results are descriptive and do not intend to show any causal relationship, they do show that in all health authority areas there are clinics that are not providing any service that is accessible to school aged young people.